Method for producing optical laminate

By incorporating a hygroscopic film and liquid crystal hardening layer in the retardation laminate, the method efficiently adjusts curl in optical laminates, addressing the inefficiencies of conventional methods and ensuring flat lamination without prolonged humidification.

JP7604236B2Active Publication Date: 2024-12-23SUMITOMO CHEM CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021003363
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-13
Publication Date
2024-12-23
Estimated Expiration
2041-01-13

AI Technical Summary

Technical Problem

Conventional methods for manufacturing optical laminates face challenges in efficiently adjusting curl deformation, particularly in thin optical laminates, which often require lengthy humidification processes due to the use of low moisture permeability films, leading to inefficiencies and potential lamination errors.

Method used

A method involving the use of a hygroscopic film and liquid crystal hardening layer in the retardation laminate, which is humidified to equilibrium moisture content, allowing for rapid moisture transfer to the polarizing plate, thereby efficiently adjusting curl by laminating the retardation laminate to a polarizing plate via an adhesive layer.

Benefits of technology

This approach significantly reduces the time required for curl adjustment, enabling the production of optical laminates with controlled curl within hours, minimizing lamination errors and ensuring flatness, even in thin configurations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604236000006
    Figure 0007604236000006
  • Figure 0007604236000001
    Figure 0007604236000001
  • Figure 0007604236000002
    Figure 0007604236000002
Patent Text Reader

Abstract

To provide a manufacturing method for an optical laminate capable of efficiently adjusting the curl of an optical laminate.SOLUTION: A manufacturing method for an optical laminate comprises a step of humidifying a retardation laminate including a hygroscopic film and a liquid crystal cured layer, and a step of obtaining a laminate in which the retardation laminate is bonded via an adhesive layer to a polarizing plate having a polarizing film and a resin film laminated on at least one surface of the polarizing film, in this order.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an optical laminate. [Background technology]

[0002] Conventionally, polarizing plates used in image display devices such as liquid crystal display devices and organic electroluminescence display devices generally consist of a polarizing film made of polyvinyl alcohol-based resin and a protective film made of triacetyl cellulose (TAC) attached with an adhesive. In recent years, protective films made of resins other than TAC have also come to be used from the viewpoints of thinning, durability, cost, productivity, etc. (e.g., Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2004-245925 A Summary of the Invention [Problem to be solved by the invention]

[0004] A retardation layer and a pressure-sensitive adhesive layer may be laminated on one side of the polarizing plate. Such an optical laminate including a polarizing plate is required to be thin, but a thin optical laminate, particularly a sheet of an optical laminate obtained by cutting from a long optical laminate, is prone to deformation such as bowing. In this specification, this deformation is also called "curl".

[0005] In order to suppress curling, a method has been used in which an optical laminate is sandwiched between a protective film and a separating film and cut out, and then humidified in a humidity control chamber. The curling of the optical laminate can be controlled by humidifying the polarizing plate. However, films with low moisture permeability are often used as the protective film and the separating film, and there is a problem that it takes a long time to humidify the polarizing plate.

[0006] An object of the present invention is to provide a method for producing an optical laminate capable of efficiently adjusting curl of the optical laminate. [Means for solving the problem]

[0007] The present invention provides a method for producing an optical laminate, the examples of which are given below. [1] A step of humidifying a retardation laminate including a hygroscopic film and a liquid crystal cured layer; A step of obtaining a laminate by bonding the retardation laminate to a polarizing plate having a polarizing film and a resin film laminated on at least one surface of the polarizing film via a pressure-sensitive adhesive layer; A method for producing an optical laminate, comprising the steps of: [2] The method according to [1], wherein the moisture-absorbing film contains a cellulose-based resin. [3] The polarizing plate has the resin film laminated on one surface of the polarizing film, The manufacturing method according to [1] or [2], wherein in the step of obtaining the laminate, the retardation laminate is laminated on the other surface of the polarizing film. [4] The method according to any one of [1] to [3], further comprising, after the step of obtaining the laminate, a step of winding up the laminate. [5] The method according to [4], further comprising the step of peeling off the hygroscopic film after the winding step. [6] The method according to any one of [1] to [5], wherein in the humidifying step, the hygroscopic film is humidified until the moisture content therein reaches an equilibrium moisture content in an environment having a temperature of 20°C or higher and 80°C or lower and a relative humidity of 45% or higher. Effect of the Invention

[0008] According to the present invention, in the method for producing an optical laminate, curl of the optical laminate can be efficiently adjusted. [Brief description of the drawings]

[0009] [Figure 1]1A to 1C are diagrams illustrating an example of a method for producing an optical laminate according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The method for producing an optical laminate according to the present invention comprises the steps of: A step of humidifying a retardation laminate including a hygroscopic film and a liquid crystal cured layer; A step of obtaining a laminate by bonding the retardation laminate to a polarizing plate having a polarizing film and a resin film laminated on at least one surface of the polarizing film via a pressure-sensitive adhesive layer; Includes, in this order.

[0011] If a retardation laminate including a hygroscopic film and a liquid crystal cured layer is pre-humidified and pasted on a polarizing plate via a pressure-sensitive adhesive layer, moisture in the hygroscopic film moves to the polarizing plate, and the polarizing plate can be humidified in a short time. The pressure-sensitive adhesive layer and the liquid crystal cured layer are unlikely to prevent the movement of moisture from the hygroscopic film to the polarizing plate. Conventionally, after a protective film, a polarizing plate, a liquid crystal cured layer, and a separate film are laminated, the optical laminate is placed in a humidified environment for 3 to 7 days to humidify the polarizing plate. According to the method of the present invention, it is not necessary to adjust the humidity of the optical laminate sandwiched between the protective film and the separate film for a long period of time. For example, sufficient humidification of the polarizing plate can be realized during a conventional storage period of several hours to several days from pasting the liquid crystal cured layer to the polarizing plate until pasting the separate film on the liquid crystal cured layer. Even if the hygroscopic film is peeled off during the process of laminating the separate film, the amount of moisture added to the polarizing plate (moisture content of the polarizing plate) can be increased compared to conventional methods of humidifying the optical laminate sandwiched between the protective film and the separate film.

[0012] The curl of the optical laminate can be adjusted by humidifying the polarizing plate. Even an optical laminate with a protective film laminated thereon is likely to curl when it is made into a sheet. There are two types of curl in the optical laminate: "normal curl" and "reverse curl." In the optical laminate, "normal curl" is curl in which the surface on the protective film side is concave, and "reverse curl" is curl in which the surface on the protective film side is convex. If reverse curl occurs, when a sheet of the optical laminate is attached to an image display element such as a liquid crystal cell or an organic EL element via its adhesive layer, it is likely to cause problems such as lamination errors or air bubbles being mixed into the interface between the adhesive layer and the image display element.

[0013] The curl of the optical laminate can be classified into two types, "MD curl" and "TD curl", in addition to the above-mentioned classification of "normal curl" and "reverse curl". "MD curl" is curl caused by stress (contraction force, expansion force, etc.) in a direction parallel to the MD direction of the long optical laminate from which the optical laminate is cut into a sheet. "TD curl" is curl caused by stress (contraction force, expansion force, etc.) in a direction parallel to the TD direction of the long optical laminate from which the optical laminate is cut into a sheet. The MD direction means the machine flow direction of the film, i.e., the longitudinal direction of the film, and the TD direction means the direction perpendicular to the MD direction.

[0014] Polarizing films, particularly polarizing films obtained by stretching polyvinyl alcohol-based resin films, have the property of expanding when they absorb moisture, and are particularly prone to expanding in the TD direction. The TD curl of the optical laminate can be adjusted by moistening the polarizing film. The forward curl / reverse curl can be adjusted by changing the position of the polarizing film in the optical laminate.

[0015] Specifically, the TD curl can be measured as a curl (curl in the absorption axis direction) in which, of the two diagonals of the measurement sample, the diagonal that has a larger angle with the absorption axis direction of the polarizing plate of the measurement sample is lifted up when a measurement sample (sheet) is cut out from a long optical laminate according to the description in the Examples section described later and the measurement sample is placed on a horizontal table with the concave side facing up. When the absorption axis direction of the polarizing plate and the MD direction of the protect film are parallel in a long polarizing plate with a protect film, the MD curl can be measured as a curl in which, of the two diagonals of the measurement sample, the diagonal that has a larger angle with the MD direction of the long optical laminate is lifted up.

[0016] <Optical laminate> The optical laminate according to the present invention includes a polarizing plate (linear polarizing plate), one or more liquid crystal cured layers, and an adhesive layer. An optical laminate including one or more liquid crystal cured layers is prone to curling, but according to the present invention, the curl can be adjusted to a desired value in a short time, so that the optical laminate can be efficiently manufactured. The optical laminate includes, for example, a protective film, a polarizing plate, an adhesive layer, a liquid crystal cured layer, and a hygroscopic film in this order. Another example of the optical laminate includes, in this order, a protective film, a polarizing plate, an adhesive layer, a liquid crystal cured layer, an adhesive layer, and a separate film.

[0017] The optical laminate may be a long object or a sheet. In this specification, the term "sheet" refers to a smaller-sized film cut out from a larger-sized film (e.g., a long (strip) film).

[0018] The length of the long optical laminate is, for example, 100 m to 20,000 m, preferably 1,000 m to 10,000 m. The width of the long optical laminate is, for example, 0.5 m to 3 m, preferably 1 m to 2.5 m.

[0019] The size, shape and cut-out angle of the optical laminate, which is a sheet, are not particularly limited. The sheet of the optical laminate is preferably square, more preferably square having long sides and short sides. This square shape is preferably rectangular. When the sheet is rectangular, the length of the long side is, for example, 50 mm to 300 mm, preferably 70 mm to 150 mm. The length of the short side is, for example, 30 mm to 200 mm, preferably 40 mm to 100 mm.

[0020] Although not particularly limited, when the shape of the sheet is rectangular, the absorption axis direction of the polarizing plate may form an angle of 45 degrees with respect to the long and short sides when viewed from the protective film side. When the shape of the sheet is rectangular, the absorption axis direction of the polarizing plate may be parallel to the long side or may form an angle of 90 degrees with respect to the long side when viewed from the protective film side.

[0021] When a sheet of the optical laminate is attached to an image display element such as a liquid crystal cell or an organic EL element via its pressure-sensitive adhesive layer, the sheet preferably does not have a reverse curl measured according to the description in the Examples section below, more preferably has a forward curl of 20 mm or less or is flat without curl, even more preferably has a forward curl of 10 mm or less or is flat without curl, and particularly preferably has a forward curl of 5 mm or less or is flat without curl. The optical laminate is preferably curled as described above in a configuration with or without a separate film, and more preferably has a curled state as described above at least in a configuration without a separate film.

[0022] <Step of Moisturizing the Retardation Laminate> Hereinafter, a method for producing an optical laminate will be described in detail with reference to Fig. 1. In this process, the moisture content of the retardation laminate 17 is increased by humidification. The retardation laminate 17 includes hygroscopic films 14, 16 and a liquid crystal cured layer 15. The hygroscopic films 14, 16, which easily absorb moisture in the air, can increase their moisture content in a short period of time.

[0023] The humidification may be performed by placing the retardation laminate 17 in an environment where the relative humidity is adjusted, for example, by introducing the retardation laminate 17 into a humidity control chamber where the relative humidity is adjusted. The long retardation laminate 17 may be introduced into the humidity control chamber and humidified while being transported along a guide roll.

[0024] The humidification may be performed in an environment with a temperature of 20° C. or higher and 80° C. or lower and a relative humidity of 45% or higher, preferably a relative humidity of 55% or higher, more preferably a relative humidity of 60% or higher, to efficiently humidify the retardation laminate 17. The relative humidity is usually 99% or lower, preferably 95% or lower.

[0025] The humidification time is not particularly limited as long as the hygroscopic films 14 and 16 included in the retardation laminate 17 are sufficiently humidified, and is, for example, 5 seconds to 120 minutes, preferably 3 minutes to 60 minutes, and more preferably 30 minutes to 60 minutes. The humidification time may be the residence time of the retardation laminate 17 in a humidity control room, or may be the transport time of the long retardation laminate 17. In the humidification step, the hygroscopic films 14 and 16 may be humidified until they reach an equilibrium moisture content.

[0026] After the humidifying step, the hygroscopic films 14 and 16 included in the retardation laminate 17 are adjusted to a moisture content higher than the equilibrium moisture content in a normal environment (temperature of about 23°C, relative humidity of about 55%) in which the laminate 103 is stored after production. For example, when the hygroscopic films 14 and 16 are triacetyl cellulose films, the moisture content after the humidifying step is preferably 1% by mass or more and 5% by mass or less, more preferably 2% by mass or more and 4.5% by mass or less, and may be 2% by mass or more and 4% by mass or less. The moisture content is measured by the dry weight method in the same manner as the equilibrium moisture content, and specifically, is calculated by the following formula: Moisture content (mass%)={(mass of retardation laminate before drying treatment−mass of retardation laminate after drying treatment) / mass of retardation laminate before drying treatment}×100 Drying refers to a process in which the film is dried at 105°C for 2 hours.

[0027] In the humidifying step, the hygroscopic films 14 and 16 included in the retardation laminate 17 are humidified so that their moisture content is higher than the equilibrium moisture content at a temperature of 23° C. and a relative humidity of 55%, thereby enabling efficient humidification of the polarizing plate 11 in a step described later. It is desirable that the humidified hygroscopic films 14 and 16 maintain or approximately maintain the moisture content after the humidification treatment until the polarizing plate 11 and the retardation laminate 17 are bonded together in a step described later.

[0028] In the humidifying process, for example, when a long film of the retardation laminate 17 is introduced into a humidity control chamber and humidified while being conveyed along a guide roll, the film unwinding speed is gradually increased toward a set speed while checking the film conveyance stability. In such a case, the time that the film at the beginning of unwinding stays in the humidity control chamber is relatively longer than the film after reaching the set speed, and the residence time of the film in the humidity control chamber varies in the MD direction. Due to this variation, the moisture content of the film after humidification varies in the MD direction, and as a result, curl distribution in the MD direction (parts with curl and parts without curl in the MD direction) may occur.

[0029] As one embodiment of the present invention, in the step of humidifying the retardation laminate 17, the moisture absorbing films 14 and 16 included in the retardation laminate 17 are humidified until they reach the equilibrium moisture content in the storage environment after the production of the laminate 103 or the environment in the step of cutting out the laminate described later, thereby suppressing the variation in moisture content in the MD direction of the retardation laminate 17, and as a result, the curl distribution in the MD direction can also be suppressed. The retardation laminate 17 is humidified until the moisture content of the moisture absorbing films 14 and 16 reaches the equilibrium moisture content in an environment at a temperature of 20° C. or higher and 80° C. or lower, and at a relative humidity of 45% or higher, more preferably at a relative humidity of 55% or higher, and even more preferably at a relative humidity of 60% or higher.

[0030] (hygroscopic film) The hygroscopic films 14, 16 are not particularly limited as long as they have high hygroscopicity, and may be, for example, a film containing a cellulose-based resin. The cellulose-based resin refers to a cellulose organic acid ester or a cellulose mixed organic acid ester in which some or all of the hydrogen atoms in the hydroxyl groups of cellulose obtained from raw cellulose such as cotton linter or wood pulp (hardwood pulp, softwood pulp) are substituted with acetyl groups, propionyl groups, and / or butyryl groups. The cellulose-based resin may be, for example, a cellulose acetate ester, a propionate ester, a butyrate ester, or a mixed ester thereof. The hygroscopic films 14, 16 preferably contain triacetyl cellulose, diacetyl cellulose, cellulose acetate propionate, or cellulose acetate butyrate. The hygroscopic films 14 and 16 may be the same film or different films. The hygroscopic films 14, 16 are preferably films made of a cellulose-based resin, and more preferably films containing triacetyl cellulose.

[0031] The thickness of the hygroscopic films 14 and 16 is usually 5 μm or more and 100 μm or less. From the viewpoint of easily retaining moisture and humidifying the polarizing plate 11 more efficiently, it is preferable that the hygroscopic films 14 and 16 are thicker.

[0032] The hygroscopic films 14 and 16 may be laminated after the formation of the liquid crystal cured layer 15, or may be used as a base film for forming the liquid crystal cured layer 15. The retardation laminate 17 may have the hygroscopic film 14 or 16 on one side or both sides of the liquid crystal cured layer 15. The hygroscopic films 14 and 16 are preferably films that can be peeled off from the liquid crystal cured layer 15.

[0033] (Liquid crystal hardening layer) The liquid crystal cured layer 15 is a retardation layer (liquid crystal cured retardation layer) composed of a cured product of a liquid crystal compound. The optical laminate may be a linear polarizer and a circular polarizer (including an elliptical polarizer) having a retardation layer. As the liquid crystal compound, it is preferable to use a polymerizable liquid crystal compound having a polymerizable group. The polymerization reaction of the polymerizable liquid crystal compound may be a thermal polymerization reaction using a thermal polymerization initiator, but is preferably a photopolymerization reaction using a photopolymerization initiator. The liquid crystal cured retardation layer can be formed using a known liquid crystal compound. The type of liquid crystal compound is not particularly limited, and a rod-shaped liquid crystal compound, a discotic liquid crystal compound, and a mixture thereof can be used.

[0034] The alignment direction of the liquid crystal compound contained in the retardation layer may be adjusted by an alignment film formed between the substrate film and the coating layer, or it can be adjusted by photo-aligning the polymerizable liquid crystal compound by irradiating it with polarized light to express or improve the alignment of the polymerizable liquid crystal compound.

[0035] The substrate film onto which the composition containing a liquid crystal compound is applied may be the above-mentioned hygroscopic film 14 or 16. The liquid crystal cured layer 15 may be laminated on the polarizing plate 11 in a form having an alignment film.

[0036] The liquid crystal cured layer 15, which is a retardation layer, may be one layer or two or more layers. Each retardation layer may have a slow axis in the same direction, or may have a slow axis in a different direction. The retardation layer may include a λ / 4 layer, and may further include at least one of a λ / 2 layer and a positive C layer. When the retardation layer includes a λ / 2 layer, the λ / 2 layer and the λ / 4 layer are laminated in order from the linear polarizer side. When the retardation layer includes a positive C layer, the λ / 4 layer and the positive C layer may be laminated in order from the linear polarizer side, or the positive C layer and the λ / 4 layer may be laminated in order from the linear polarizer side. The thickness of the liquid crystal cured layer 15 is, for example, 0.1 μm or more and 10 μm or less, preferably 0.5 μm or more and 8 μm or less, and more preferably 0.5 μm or more and 4 μm or less. From the viewpoint of more efficiently humidifying the polarizer 11, it is preferable that the liquid crystal cured layer 15 is thin.

[0037] <Step of Obtaining a Laminate in Which a Retardation Laminate is Bonded to a Polarizing Plate> In this step, the retardation laminate 17 is attached to the polarizing plate 11 via the adhesive layer 12. When the protective film 10 is laminated on the polarizing plate 11 (laminate 101), the adhesive layer 12 and the retardation laminate 17 are laminated on the surface of the polarizing plate 11 opposite to the side on which the protective film 10 is laminated.

[0038] The obtained laminate 103 is preferably long. The length of the long laminate 103 is, for example, 100 m or more and 20,000 m or less, and preferably 1,000 m or more and 10,000 m or less. The width of the long laminate 103 is, for example, 0.5 m or more and 3 m or less, and preferably 1 m or more and 2.5 m or less.

[0039] The polarizing plate 11 and the retardation laminate 17 can be bonded together, for example, by continuously transporting the long polarizing plate 11 and the long retardation laminate 17, stacking the polarizing plate 11 and the retardation laminate 17, and passing them between a pair of laminating rolls to sandwich them, thereby producing a laminate 103 in which both films are bonded together.

[0040] The adhesive layer 12 may be laminated on the surface of the polarizing plate 11 before the retardation laminate 17 is laminated. Prior to lamination of the polarizing plate 11 and the retardation laminate 17, at least one of the bonding surfaces may be subjected to a surface activation treatment such as plasma treatment, corona treatment, ultraviolet irradiation treatment, flame (flame) treatment, or saponification treatment. A separate film 13 may be laminated on the adhesive layer 12 side of the polarizing plate 11 (laminate 102). In this case, the separate film 13 is usually peeled off and removed when the retardation laminate 17 is laminated.

[0041] When the retardation laminate 17 has the hygroscopic films 14 and 16 on both sides of the liquid crystal cured layer 15, it is preferable to peel off the hygroscopic film 14 on one side and attach the liquid crystal cured layer 15 side to the polarizing plate 11. When the retardation laminate 17 has the hygroscopic film 16 on one side of the liquid crystal cured layer 15 and a base layer on the other side, it is preferable to peel off the base layer and attach the laminate including the liquid crystal cured layer 15 and the hygroscopic film 16 to the polarizing plate 11 so that the liquid crystal cured layer 15 side is laminated.

[0042] When the polarizing plate 11 is a single-sided protected polarizing plate in which a resin film is laminated on one side of the polarizing film, it is preferable that a retardation laminate 17 is laminated on the other side of the polarizing film (the side on which the resin film is not laminated) in order to humidify the polarizing plate 11 more efficiently.

[0043] (Polarizing plate) The polarizing plate 11 is a linear polarizing plate including a polarizing film, and a resin film is laminated on one or both sides of the polarizing film. The polarizing plate 11 having a resin film on only one side of the polarizing film is advantageous for making the polarizing plate 11 thinner.

[0044] The thickness of the polarizing plate 11 is usually 5 μm or more and 150 μm or less, and from the viewpoint of thinning the polarizing plate 11, it is preferably 80 μm or less, more preferably 70 μm or less, and even more preferably 60 μm or less, 50 μm or less, or 40 μm or less. The smaller the thickness of the polarizing plate 11, the more likely the optical laminate is to curl, but according to the present invention, even if the thickness of the polarizing plate 11 is small, the curl of the optical laminate can be efficiently adjusted. The thickness of the polarizing plate 11 may be 20 μm or more, 25 μm or more, or 30 μm or more.

[0045] (Polarizing film) A polarizing film has the property of absorbing linearly polarized light having a vibration plane parallel to the absorption axis and transmitting linearly polarized light having a vibration plane perpendicular to the absorption axis (parallel to the transmission axis). One example of a polarizing film is a polarizing film in which a dichroic dye is adsorbed and oriented on a uniaxially stretched polyvinyl alcohol-based resin film. Such a polarizing film can be produced, for example, by a method including a step of uniaxially stretching a polyvinyl alcohol-based resin film; a step of dyeing the polyvinyl alcohol-based resin film with the dichroic dye to adsorb the dichroic dye; a step of treating the polyvinyl alcohol-based resin film with the adsorbed dichroic dye with a crosslinking liquid such as an aqueous boric acid solution; and a step of washing with water after the treatment with the crosslinking liquid.

[0046] As the polyvinyl alcohol resin, a saponified polyvinyl acetate resin can be used. As the polyvinyl acetate resin, in addition to polyvinyl acetate, which is a homopolymer of vinyl acetate, copolymers of vinyl acetate with other monomers copolymerizable therewith can be mentioned. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and (meth)acrylamides having an ammonium group.

[0047] In this specification, "(meth)acrylic" means at least one selected from acrylic and methacrylic. The same applies to "(meth)acryloyl", "(meth)acrylate", etc.

[0048] The saponification degree of the polyvinyl alcohol resin is usually 85 mol% or more and 100 mol% or less, and preferably 98 mol% or more. The polyvinyl alcohol resin may be modified, and for example, polyvinyl formal or polyvinyl acetal modified with aldehydes can be used. The average polymerization degree of the polyvinyl alcohol resin is usually 1000 or more and 10000 or less, and preferably 1500 or more and 5000 or less. The saponification degree and average polymerization degree of the polyvinyl alcohol resin can be determined in accordance with JIS K 6726.

[0049] The film of such polyvinyl alcohol-based resin is used as the original film of the polarizing film. The method of forming the polyvinyl alcohol-based resin is not particularly limited, and a known method is adopted. The thickness of the polyvinyl alcohol-based resin film is not particularly limited, but is, for example, about 10 μm or more and 150 μm or less, preferably 50 μm or less, more preferably 35 μm or less.

[0050] The uniaxial stretching of the polyvinyl alcohol-based resin film can be performed before, simultaneously with, or after dyeing with a dichroic dye. When the uniaxial stretching is performed after dyeing, the uniaxial stretching may be performed before or during a crosslinking treatment. The uniaxial stretching may also be performed in a plurality of these stages.

[0051] In the uniaxial stretching, the film may be stretched uniaxially between rolls having different peripheral speeds, or may be stretched uniaxially using a heated roll. The uniaxial stretching may be dry stretching in which stretching is performed in the atmosphere, or wet stretching in which stretching is performed in a state where the polyvinyl alcohol-based resin film is swollen using a solvent or water. The stretching ratio is usually 3 times or more and 8 times or less.

[0052] As a method for dyeing a polyvinyl alcohol-based resin film with a dichroic dye, for example, a method of immersing the film in an aqueous solution containing the dichroic dye is adopted. As the dichroic dye, iodine or a dichroic organic dye is used. It is preferable that the polyvinyl alcohol-based resin film is immersed in water before the dyeing process.

[0053] As a crosslinking treatment after dyeing with a dichroic dye, a method of immersing the dyed polyvinyl alcohol resin film in an aqueous solution containing boric acid is usually adopted. When iodine is used as the dichroic dye, the aqueous solution containing boric acid preferably contains potassium iodide.

[0054] The polyvinyl alcohol-based resin film after the crosslinking treatment is usually washed with water. The washing can be performed, for example, by immersing the crosslinked polyvinyl alcohol-based resin film in water. The temperature of the water used in the washing is usually about 1°C or higher and 40°C or lower.

[0055] After washing with water, the film is dried to obtain a polarizing film. The drying can be performed by a hot air dryer, by contacting with a heated roll, by a far-infrared heater, etc. The temperature for the drying is usually about 30°C or higher and 100°C or lower, and preferably 50°C or higher and 90°C or lower.

[0056] The moisture content of the polarizing film is reduced to a practical level by the drying treatment. The moisture content is usually 5% by mass or more and 20% by mass or less, and preferably 8% by mass or more and 15% by mass or less. If the moisture content is less than 5% by mass, the polarizing film loses its flexibility and may be damaged or broken after drying. If the moisture content is more than 20% by mass, the polarizing film may have poor thermal stability. The moisture content referred to here is measured by the dry weight method, and the measurement method is as described above.

[0057] The thickness of the polarizing film is usually about 2 μm or more and 40 μm or less. From the viewpoint of thinning the polarizing plate 11, the thickness of the polarizing film is preferably 20 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less. The thicker the polarizing film, the more likely the optical laminate is to curl. However, according to the present invention, even if the polarizing film has a thickness of, for example, 10 μm or more, further 15 μm or more, and particularly 20 μm or more, the curl of the optical laminate can be efficiently controlled.

[0058] (Resin film) The resin film is a film made of a thermoplastic resin having light transmission, preferably an optically transparent thermoplastic resin. Examples of the resin film include cyclopolyolefin-based resin film; cellulose-based resin film made of resin such as triacetyl cellulose and diacetyl cellulose; polyester-based resin film made of resin such as polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate; polycarbonate-based resin film; (meth)acrylic resin film; polypropylene-based resin film, and other films known in the art. The resin film is preferably a cellulose-based resin film, more preferably a resin film containing triacetyl cellulose.

[0059] From the viewpoint of thinning the optical laminate, the thickness of the resin film is usually 100 μm or less, preferably 80 μm or less, more preferably 60 μm or less, even more preferably 40 μm or less, and even more preferably 30 μm or less. The thickness of the resin film is usually 5 μm or more, preferably 10 μm or more. The thinner the resin film, the more likely the optical laminate is to curl, but according to the present invention, even if the thickness of the resin film is as thin as, for example, 40 μm or less, or even 30 μm or less, curling can be efficiently controlled.

[0060] The resin film can be a protective film that protects the polarizing film. The resin film may also have optical functions such as a retardation film and a brightness enhancement film. For example, a thermoplastic resin film made of the above-mentioned material can be stretched (uniaxially or biaxially stretched, etc.) to form a retardation film having an arbitrary retardation value. The resin film may have a surface treatment layer (coating layer) such as a hard coat layer, an antiglare layer, an antireflection layer, an antistatic layer, or an antifouling layer on its surface.

[0061] The resin film can be attached to the polarizing film via an adhesive layer or a pressure-sensitive adhesive layer. The resin film is preferably attached to the polarizing film via an adhesive layer. As the adhesive for forming the adhesive layer, a water-based adhesive, an active energy ray curable adhesive, or a heat-curable adhesive can be used, and a water-based adhesive or an active energy ray curable adhesive is preferable.

[0062] Examples of the aqueous adhesive include an adhesive made of an aqueous polyvinyl alcohol resin solution, an aqueous two-liquid urethane emulsion adhesive, and the like. Among them, an aqueous adhesive made of an aqueous polyvinyl alcohol resin solution is preferably used. Examples of the polyvinyl alcohol resin include a vinyl alcohol homopolymer obtained by saponifying polyvinyl acetate, which is a homopolymer of vinyl acetate, a polyvinyl alcohol copolymer obtained by saponifying a copolymer of vinyl acetate and another monomer copolymerizable therewith, and a modified polyvinyl alcohol polymer in which the hydroxyl groups of these are partially modified. The aqueous adhesive may contain a crosslinking agent such as an aldehyde compound (such as glyoxal), an epoxy compound, a melamine compound, a methylol compound, an isocyanate compound, an amine compound, or a polyvalent metal salt.

[0063] When a water-based adhesive is used, it is preferable to carry out a drying step to remove water contained in the water-based adhesive after laminating the polarizing film and the resin film. After the drying step, a curing step may be carried out, for example, at a temperature of 20° C. or higher and 45° C. or lower.

[0064] The active energy ray-curable adhesive is an adhesive containing a curable compound that is cured by irradiation with active energy rays such as ultraviolet rays, visible light, electron beams, and X-rays, and is preferably an ultraviolet ray-curable adhesive.

[0065] The curable compound may be a cationic polymerizable curable compound or a radical polymerizable curable compound. Examples of the cationic polymerizable curable compound include an epoxy compound (a compound having one or more epoxy groups in the molecule), an oxetane compound (a compound having one or more oxetane rings in the molecule), or a combination thereof. Examples of the radical polymerizable curable compound include a (meth)acrylic compound (a compound having one or more (meth)acryloyloxy groups in the molecule), other vinyl compounds having a radical polymerizable double bond, or a combination thereof. A cationic polymerizable curable compound and a radical polymerizable curable compound may be used in combination. An active energy ray curable adhesive usually further includes a cationic polymerization initiator and / or a radical polymerization initiator for initiating the curing reaction of the curable compound.

[0066] When laminating a polarizing film and a resin film, at least one of the laminating surfaces may be subjected to a surface activation treatment in order to enhance adhesion. Examples of the surface activation treatment include dry treatments such as corona treatment, plasma treatment, discharge treatment (glow discharge treatment, etc.), flame treatment, ozone treatment, UV ozone treatment, and ionizing active ray treatment (ultraviolet ray treatment, electron beam treatment, etc.); and wet treatments such as ultrasonic treatment using a solvent such as water or acetone, saponification treatment, and anchor coat treatment. These surface activation treatments may be performed alone or in combination of two or more.

[0067] When resin films are laminated to both sides of the polarizing film, the adhesive for laminating these resin films may be the same type of adhesive or different types of adhesive.

[0068] (Adhesive layer) The adhesive layer 12 bonds the polarizing plate 11 and the retardation laminate 17. The adhesive layer 12 can be composed of an adhesive composition mainly composed of (meth)acrylic resin, rubber resin, urethane resin, ester resin, silicone resin, or polyvinyl ether resin. Among them, an adhesive composition having a (meth)acrylic resin as a base polymer, which is excellent in transparency, weather resistance, heat resistance, etc., is preferable. The adhesive composition may be of an active energy ray curing type or a heat curing type.

[0069] As the (meth)acrylic resin (base polymer) used in the pressure-sensitive adhesive composition, a polymer or copolymer containing one or more monomers of (meth)acrylic acid esters such as butyl (meth)acrylate, ethyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, etc. is preferably used. A polar monomer is preferably copolymerized in the base polymer. Examples of the polar monomer include monomers having a carboxyl group, a hydroxyl group, an amide group, an amino group, an epoxy group, etc., such as a (meth)acrylic acid compound, a 2-hydroxypropyl (meth)acrylate compound, a hydroxyethyl (meth)acrylate compound, a (meth)acrylamide compound, an N,N-dimethylaminoethyl (meth)acrylate compound, and a glycidyl (meth)acrylate compound.

[0070] The adhesive composition may contain only the base polymer, but usually further contains a crosslinking agent. Examples of the crosslinking agent include divalent or higher metal ions that form carboxylate metal salts with carboxyl groups; polyamine compounds that form amide bonds with carboxyl groups; polyepoxy compounds or polyols that form ester bonds with carboxyl groups; and polyisocyanate compounds that form amide bonds with carboxyl groups. Among these, polyisocyanate compounds are preferred.

[0071] The active energy ray curable adhesive composition has a property of being cured by irradiation with active energy rays such as ultraviolet rays and electron beams, and has a property of being able to adhere to an adherend such as a film even before irradiation with active energy rays, and is able to adjust the adhesive strength by being cured by irradiation with active energy rays. The active energy ray curable adhesive composition is preferably an ultraviolet ray curable type. The active energy ray curable adhesive composition further contains an active energy ray polymerizable compound in addition to a base polymer and a crosslinking agent. If necessary, a photopolymerization initiator, a photosensitizer, etc. may be contained.

[0072] The pressure-sensitive adhesive composition can contain additives such as microparticles for imparting light scattering properties, beads (resin beads, glass beads, etc.), glass fibers, resins other than the base polymer, antistatic agents, tackifiers, fillers (metal powders and other inorganic powders, etc.), antioxidants, UV absorbers, dyes, pigments, colorants, defoamers, and corrosion inhibitors.

[0073] The adhesive layer 12 can be formed by dissolving or dispersing an adhesive composition in an organic solvent such as toluene or ethyl acetate to prepare an adhesive liquid, applying this to the polarizing plate 11, and drying it. The adhesive layer 12 may be formed in a sheet shape on a release-treated separate film 13, and then transferred to the target surface of the polarizing plate 11. When an active energy ray-curable adhesive composition is used, the formed adhesive layer 12 can be irradiated with active energy rays to form a cured product having a desired degree of cure.

[0074] The thickness of the pressure-sensitive adhesive layer 12 is usually from 1 μm to 40 μm, but from the viewpoint of reducing the thickness of the optical laminate, it is preferably from 2 μm to 30 μm.

[0075] (Separate film) The separate film 13 is a film that is temporarily attached in order to protect the surface of the pressure-sensitive adhesive layer 12 until it is attached to an image display element or other optical components. The separate film 13 is usually made of a thermoplastic resin film having one side subjected to a release treatment using a silicone-based, fluorine-based or other release agent, and the release-treated surface is attached to the pressure-sensitive adhesive layer 12.

[0076] The thermoplastic resin constituting the separate film 13 may be, for example, a polyethylene-based resin such as polyethylene, a polypropylene-based resin such as polypropylene, a polyester-based resin such as polyethylene terephthalate, polyethylene naphthalate, etc. The thickness of the separate film 13 is, for example, 10 μm or more and 50 μm or less.

[0077] (Protection film) A protective film 10 may be laminated on the polarizing plate 11. The protective film 10 is a peelable film for protecting the surface of the polarizing plate 11. When the optical laminate is distributed on the market, the protective film 10 is often attached. The protective film 10 is attached to the surface of the polarizing plate 11 on the side opposite to the side on which the liquid crystal cured layer 15 and the adhesive layer 12 are laminated. The protective film 10 is composed of, for example, an adhesive layer and a base film laminated via the adhesive layer. The protective film 10 is usually peeled off and removed together with the adhesive layer after the optical laminate is attached to, for example, an image display element or the like.

[0078] The base film of the protective film 10 may be made of a thermoplastic resin, such as a polyolefin resin, for example, a polyethylene resin, a polypropylene resin, or a cyclic polyolefin resin; a polyester resin, such as polyethylene terephthalate or polyethylene naphthalate; a polycarbonate resin; or a (meth)acrylic resin. The base film may have a single layer structure or a multilayer structure. The adhesive layer of the protective film 10 may be made of a (meth)acrylic adhesive, an epoxy adhesive, a urethane adhesive, a silicone adhesive, or the like. The protective film 10 may be a resin film having self-adhesive properties, such as a polypropylene resin or a polyethylene resin. In this case, the protective film 10 does not have an adhesive layer.

[0079] The thickness of the protective film 10 can be, for example, 5 μm or more and 150 μm or less, preferably 10 μm or more and 100 μm or less, more preferably 20 μm or more and 75 μm or less, and even more preferably 25 μm or more and 70 μm or less (for example, 60 μm or less, and even more preferably 55 μm or less). If the thickness of the protective film 10 is less than 5 μm, the protection of the polarizing plate 11 may be insufficient, and it is also disadvantageous in terms of handling. If the thickness of the protective film 10 exceeds 150 μm, it is disadvantageous in terms of thinning of the optical laminate and reworkability of the protective film 10.

[0080] <Step of Winding the Laminate> When the laminate 103 of the polarizing plate 11 and the retardation laminate 17 is long, the laminate 103 may be sequentially wound around a winding roll, or may be subjected to a step of laminating the separation film 19 or a step of peeling off the hygroscopic film 16 described below without being wound. Usually, when manufacturing a long optical laminate, a long object is wound up for each lamination step. Before the wound laminate 103 is used in the next step, the moisture in the retardation laminate 17 is sufficiently transferred to the polarizing plate 11. For example, when the laminate 103 including the protective film 10, the polarizing plate 11, the adhesive layer 12, the liquid crystal cured layer 15, and the hygroscopic film 16 in this order is wound up into a roll form, the area of ​​the hygroscopic film 16 exposed to air is reduced, so that the moisture can be transferred to the polarizing plate 11 more quickly.

[0081] After obtaining the laminate 103 of the polarizing plate 11 and the retardation laminate 17, it is preferable to wind up the laminate 103 without carrying out a step of drying the laminate 103.

[0082] <Process for peeling off the moisture absorbing film> After laminating the retardation laminate 17 on the polarizing plate 11, the hygroscopic film 16 is peeled off and removed from the laminate 103, preferably leaving the liquid crystal cured layer 15. The hygroscopic film 16 may be peeled off as it is after laminating the retardation laminate 17 on the polarizing plate 11, or may be once wound up on a roll (the above-mentioned winding step) and then peeled off while unwinding in a subsequent step.

[0083] The optical laminate from which the hygroscopic film 16 has been removed may further have a separate film 19 attached thereto via an adhesive layer 18 (laminate 104). The separate film 19 and the adhesive layer 18 may be the same as the above-mentioned separate film 13 and the adhesive layer 12, respectively.

[0084] <Step of cutting out the laminate> When the laminate obtained by the above-mentioned method is long, it is preferable to cut out a sheet from the long laminate. The cutting (cutting) can be performed using a conventionally known cutting means such as a cutting cutter. The size, shape and cutting angle of the sheet are as described in the above <Optical laminate>.

[0085] The sheet immediately after being cut out has a reverse curl of 10 mm or less, more preferably 5 mm or less, is flat without curl, or is in a positive curl state. By adjusting in this way, the process of final curl adjustment described later is unnecessary, or the time required for the process of final curl adjustment can be shortened.

[0086] <Final curl adjustment process> If the sheet obtained by the above method has reverse curl, it is adjusted by humidifying it appropriately. The humidification can be performed by placing the sheet in an environment with a controlled relative humidity, for example, by storing the sheet in a humidity-controlled room with a controlled relative humidity. EXAMPLES

[0087] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto. In the examples, "%" and "parts" are by mass % and parts by mass unless otherwise specified.

[0088] [Method of measuring curl] A diamond-shaped cut-out piece with a long side of 155 mm and a short side of 78 mm, with its diagonal lines parallel to the MD and TD directions, was cut out from the laminate 104, and the separate film 19 was peeled off from the cut-out piece to prepare a test piece. After sufficiently neutralizing the test piece, the concave side of the test piece was placed on a reference surface (horizontal table) and the height from the reference surface was measured for each of the four corners of the test piece. When the test piece was placed on the reference surface with the protective film side facing up, and the corners of the test piece rose, this curl was taken as a positive curl, and the height of the corners from the reference surface was expressed as a positive numerical value. On the other hand, when the test piece was placed on the reference surface with the protective film side facing down and the corners of the test piece rose, this curl was taken as a reverse curl, and the height of the corners from the reference surface was expressed as a negative numerical value.

[0089] The measured MD curl value was the average value of the heights from the reference plane of two corners on a diagonal line parallel to the MD direction. The measured TD curl value was the average value of the heights from the reference plane of two corners on a diagonal line parallel to the TD direction. If the MD curl value and the TD curl value are positive or 0, it indicates that reverse curl is suppressed, and if the value is negative, the larger the absolute value, the more reverse curl has progressed.

[0090] [Method for measuring moisture content of optical laminate] A diamond-shaped piece with long sides of 155 mm and short sides of 78 mm, with its diagonals parallel to the MD and TD directions, was cut out from the laminate 104, and the separate film 19 was peeled off from the cut piece to prepare a test piece. The test piece was dried at 105° C. for 2 hours, and the mass after drying was compared with the mass before drying to determine the moisture content of the optical laminate. Moisture content (mass%)={(mass of optical laminate before drying treatment−mass of optical laminate after drying treatment) / mass of optical laminate before drying treatment}×100

[0091] [Preparation of adhesive layer] The adhesive layer was produced by the following method. 97.0 parts of n-butyl acrylate, 1.0 part of acrylic acid, 0.5 parts of 2-hydroxyethyl acrylate, 200 parts of ethyl acetate, and 0.08 parts of 2,2'-azobisisobutyronitrile were charged into a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping device, and a nitrogen inlet tube, and the air in the reaction vessel was replaced with nitrogen gas. The reaction solution was heated to 60°C while stirring and reacted for 6 hours, and then cooled to room temperature. When the weight average molecular weight of a portion of the obtained solution was measured, it was confirmed that a (meth)acrylic acid ester polymer of 1.8 million was obtained.

[0092] 100 parts of the obtained (meth)acrylic acid ester polymer (solid content equivalent; the same applies below), 0.30 parts of trimethylolpropane-modified tolylene diisocyanate (manufactured by Tosoh Corporation, product name "Coronate L") as an isocyanate-based crosslinking agent, and 0.30 parts of 3-glycidoxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., product name "KBM403") as a silane coupling agent were mixed and thoroughly stirred. This was diluted with ethyl acetate to obtain a coating solution of the adhesive composition.

[0093] A coating solution of the adhesive composition was applied with an applicator to the release-treated surface (release surface) of a first separate film (manufactured by Lintec Corporation: SP-PLR382190) forming a release layer so that the thickness after drying would be 25 μm, and an adhesive layer was formed by drying at 100° C. for 1 minute. A second separate film (manufactured by Lintec Corporation: SP-PLR381031) was attached to the surface of the adhesive layer opposite to the surface to which the first separate film was attached, to obtain an adhesive layer with double-sided separate films.

[0094] [Preparation of polarizing plate (101) with protective film] A 20 μm thick polyvinyl alcohol film (average polymerization degree about 2400, saponification degree 99.9 mol% or more) was uniaxially stretched about 5 times by dry stretching. While maintaining tension, it was immersed in pure water at 60°C for 1 minute, and then immersed in an aqueous solution with a mass ratio of iodine / potassium iodide / water of 0.05 / 5 / 100 at 28°C for 60 seconds. It was then immersed in an aqueous solution with a mass ratio of potassium iodide / boric acid / water of 8.5 / 8.5 / 100 at 72°C for 300 seconds. It was washed with pure water at 26°C for 20 seconds and dried at 65°C to obtain a polarizing film with a thickness of 7 μm in which iodine was adsorbed and aligned on the polyvinyl alcohol film.

[0095] An epoxy adhesive was applied to one side of the polarizing film, and a transparent norbornene resin film with a thickness of 13 μm was attached as a protective layer. The epoxy adhesive was prepared by dissolving 3 parts of carboxyl-modified polyvinyl alcohol (Kuraray Co., Ltd., product name "KL-318") in 100 parts of water, and adding 1.5 parts of a polyamide epoxy additive (Taoka Chemical Co., Ltd., product name "Sumirez Resin 650 (30)", an aqueous solution with a solid content of 30%), which is a water-soluble epoxy resin. In this way, a polarizing plate in which a resin film was laminated on one side of the polarizing film was obtained.

[0096] A protective film consisting of a 15 μm thick acrylic adhesive layer formed on a 38 μm thick polyethylene terephthalate (PET) film was attached to the surface of the resin film opposite the polarizing film, to obtain a polarizing plate 101 with a protective film having a thickness of 73 μm.

[0097] [Preparation of Retardation Laminate] (Manufacture of the first liquid crystal cured layer) A cycloolefin polymer (COP) film having a thickness of 50 μm was treated once using a corona treatment device (AGF-B10, manufactured by Kasuga Electric Co., Ltd.) under the conditions of an output of 0.3 kW and a treatment speed of 3 m / min. The surface that had been subjected to the corona treatment was coated with the following composition for forming an alignment layer (1) using a bar coater, dried at 80° C. for 1 minute, and then irradiated with 100 mJ / cm 2 using a polarized UV irradiation device (SPOT CURE SP-7, manufactured by Ushio Inc.). 2An alignment layer was obtained by carrying out polarized UV exposure with an integrated light amount of 100 nm. The thickness of the alignment layer was measured with a laser microscope (LEXT, manufactured by Olympus Corporation) and found to be 100 nm.

[0098] Next, the following liquid crystal layer forming composition (A-1) was applied onto the alignment layer using a bar coater and dried at 120°C for 1 minute, and then irradiated with ultraviolet light using a high-pressure mercury lamp (Unicur VB-15201BY-A, manufactured by Ushio Inc.) (under a nitrogen atmosphere, wavelength: 365 nm, accumulated light amount at wavelength 365 nm: 1000 mJ / cm 2 ) to form a first liquid crystal cured layer as a retardation layer, thereby obtaining a first liquid crystal cured layer with a base layer. The thickness of the first liquid crystal cured layer was 2 μm.

[0099] (Preparation of Orientation Layer-Forming Composition (1)) The alignment material was mixed with the following solvent and stirred at a temperature of 80° C. for 1 hour to obtain an alignment layer forming composition (1). Oriented materials (part 5): [ka] Solvent (95 parts): Cyclopentanone

[0100] (Preparation of Liquid Crystal Layer Forming Composition (A-1)) A polymerizable liquid crystal compound and a polymerization initiator were mixed in the following solvent and stirred at 80° C. for 1 hour to obtain a liquid crystal layer forming composition (A-1). The polymerizable liquid crystal compound A1 and the polymerizable liquid crystal compound A2 were synthesized by the method described in JP-A-2010-31223. ·Polymerizable liquid crystal compound A1 (80 parts): [ka] ·Polymerizable liquid crystal compound A2 (20 parts): [ka] Polymerization initiator (6 parts): 2-Dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one (manufactured by Ciba Specialty Chemicals, "Irgacure 369") Solvent (400 parts): Cyclopentanone

[0101] (Manufacture of the second liquid crystal cured layer) A hygroscopic film, a triacetyl cellulose (TAC) film having a thickness of 80 μm, was treated once using a corona treatment device (AGF-B10, manufactured by Kasuga Electric Co., Ltd.) under the conditions of an output of 0.3 kW and a treatment speed of 3 m / min. The corona-treated surface was coated with the following composition for forming an alignment layer (2) using a bar coater and dried at 90° C. for 1 minute to obtain an alignment layer. The thickness of the obtained alignment layer was measured with a laser microscope (LEXT, manufactured by Olympus Corporation) and found to be 34 nm.

[0102] Next, the following liquid crystal layer forming composition (B-1) was applied onto the alignment layer using a bar coater and dried at 90°C for 1 minute, and then irradiated with ultraviolet light using a high-pressure mercury lamp (Unicur VB-15201BY-A, manufactured by Ushio Inc.) (under a nitrogen atmosphere, wavelength: 365 nm, accumulated light amount at wavelength 365 nm: 1000 mJ / cm 2 ) to form a second liquid crystal cured layer as a retardation layer, thereby obtaining a second liquid crystal cured layer with a hygroscopic film. The thickness of the second liquid crystal cured layer was 1 μm.

[0103] (Preparation of Orientation Layer Forming Composition (2)) 2-Butoxyethanol was added to the oriented polymer Sunever SE-610 (manufactured by Nissan Chemical Industries, Ltd.) to obtain an orientation layer forming composition (2). The obtained orientation layer forming composition (2) had a solid content of 1% relative to the total amount of the composition, and a solvent content of 99% relative to the total amount of the composition. The solid content of Sunever SE-610 was calculated from the concentration listed in the delivery specifications.

[0104] (Preparation of Liquid Crystal Layer Forming Composition (B-1)) A polymerizable liquid crystal compound, a polymerization initiator, and a reactive additive were mixed in the following solvent, stirred at 80° C. for 1 hour, and then cooled to room temperature to obtain a liquid crystal layer forming composition (B-1). Polymerizable liquid crystal compound LC242 (BASF) (19.2%): [ka] Polymerization initiator (0.5%): Irgacure (registered trademark) 907 (BASF Japan Ltd.) Reactive additive (1.1%): Laromer (registered trademark) LR-9000 (BASF Japan) Solvent (79.1%): Propylene glycol 1-monomethyl ether 2-acetate

[0105] (Preparation of Adhesive Composition) The cationic curable components a1 to a3 and a cationic polymerization initiator shown below were mixed. The cationic polymerization initiator and a sensitizer shown below were further mixed, and the mixture was defoamed to prepare a photocurable adhesive composition. The following blend amounts are based on the solid content. Cationic curing component a1 (70 parts): 3',4'-Epoxycyclohexylmethyl 3',4'-epoxycyclohexanecarboxylate (product name: CEL2021P, manufactured by Daicel Corporation) Cationic curing component a2 (20 parts): Neopentyl glycol diglycidyl ether (product name: EX-211, manufactured by Nagase ChemteX Corporation) Cationic curing component a3 (10 parts): 2-Ethylhexyl glycidyl ether (product name: EX-121, manufactured by Nagase ChemteX Corporation) Cationic polymerization initiator (2.25 parts): Product name: CPI-100 (San-Apro Co., Ltd.) 50% propylene carbonate solution Sensitizer (2 parts): 1,4-Diethoxynaphthalene

[0106] (Production of Retardation Laminate) The surface of the second liquid crystal cured layer with the hygroscopic film on the side of the second liquid crystal cured layer was subjected to corona treatment (800 W, 10 m / min). The adhesive composition was applied to this corona-treated surface using a coater so that the thickness of the adhesive layer was 1 μm. Next, the first liquid crystal cured layer side of the first liquid crystal cured layer with the substrate layer was subjected to corona treatment under the same conditions as above, and the coating layer of the adhesive composition formed on the second liquid crystal cured layer with the hygroscopic film was laminated. The adhesive composition was cured by irradiating ultraviolet rays from the second liquid crystal cured layer side using an ultraviolet irradiation device, and a retardation laminate 17 having a hygroscopic film 16 laminated on one side was obtained. The irradiation conditions were an irradiation intensity of 390 mW / cm in the UVA region. 2 , the cumulative light intensity is 420mJ / cm 2 So, in the UVB range, it is 400mW / cm 2 , the cumulative light intensity is 400mJ / cm 2 It was made so that:

[0107] [Example 1] An optical laminate was obtained using the retardation laminate 17, the polarizing plate 101 with the protective film, and the pressure-sensitive adhesive layer with the double-sided separate film prepared above.

[0108] The surface of the polarizing plate 101 with the protective film opposite to the protective film 10 side was subjected to corona treatment (800 W, 10 m / min). The second separate film was peeled off from the adhesive layer with double-sided separate films prepared above. The corona-treated surface of the polarizing plate 11 and the peeled surface of the second separate film of the adhesive layer were attached to obtain a polarizing plate 102 with a first separate film 13.

[0109] The retardation laminate 17 was left for 40 minutes in an environment of 23°C temperature and 55% humidity, and then the surface (the surface on the first liquid crystal cured layer side) of the retardation laminate 17 exposed by peeling off the COP film was bonded to the adhesive layer 12 exposed by peeling off the first separate film 13 from the polarizing plate 102 with the first separate film 13, to obtain a laminate 103 in which the polarizing plate 11 and the liquid crystal cured layer 15 were laminated via the adhesive layer 12. Thereafter, the laminate 103 was packed in an aluminum moisture-proof bag and stored in an environment of 23°C temperature and 55% humidity for 24 hours.

[0110] After 24 hours, the TAC film (hygroscopic film 16) was peeled off from the laminate 103, and the exposed surface (the surface of the second liquid crystal cured layer side of the liquid crystal cured layer 15) was bonded to the pressure-sensitive adhesive layer exposed by peeling off the second separate film from the pressure-sensitive adhesive layer with double-sided separate films, to obtain a laminate 104 having a pressure-sensitive adhesive layer 18 and a first separate film 19. The laminate 104 was cut into a rectangular sheet of a predetermined size to obtain an optical laminate A. The curl of the obtained optical laminate A was measured, and the TD curl value of the optical laminate A was calculated. In addition, the moisture content of the optical laminate A was measured by the dry weight method. The results are shown in Table 1.

[0111] [Example 2] An optical laminate B was obtained in the same manner as in Example 1, except that the retardation laminate 17 was left for 5 minutes in an environment of a temperature of 23°C and a humidity of 55%. The curl of the obtained optical laminate B was measured, and the TD curl value of the optical laminate B was calculated. In addition, the moisture content of the optical laminate B was measured by a dry weight method. The results are shown in Table 1.

[0112] [Comparative Example 1] An optical laminate C was obtained in the same manner as in Example 1 without humidifying the retardation laminate 17. The curl of the obtained optical laminate C was measured to calculate the TD curl value of the optical laminate C. In addition, the moisture content of the optical laminate C was measured by the dry weight method. The results are shown in Table 1.

[0113] [Table 1]

[0114] Table 1 shows that the moisture contents of the optical laminates A and B obtained in Examples 1 and 2 are higher than that of the optical laminate C obtained in Comparative Example 1. It is presumed that moisture was efficiently transferred from the hygroscopic film to the polarizing plate, so that the polarizing plate was sufficiently humidified, and as a result, reverse curl was suppressed. [Explanation of symbols]

[0115] 10 protection film, 11 polarizing plate, 12, 18 adhesive layer, 13, 19 separation film, 14, 16 moisture absorbing film, 15 liquid crystal curing layer, 17 retardation laminate.

Claims

1. A step of humidifying a retardation laminate including a hygroscopic film and a liquid crystal cured layer; A step of obtaining a laminate by bonding the retardation laminate to a polarizing plate having a polarizing film and a resin film laminated on at least one surface of the polarizing film via a pressure-sensitive adhesive layer; in that order, The method for producing an optical laminate further comprises a step of peeling off the moisture absorbing film.

2. The method according to claim 1 , wherein the moisture-absorbing film comprises a cellulose-based resin.

3. The polarizing plate has the resin film laminated on one surface of the polarizing film, The method according to claim 1 or 2, wherein in the step of obtaining the laminate, the retardation laminate is laminated on the other surface of the polarizing film.

4. The method according to any one of claims 1 to 3, further comprising a step of winding up the laminate after the step of obtaining the laminate.

5. The manufacturing method described in claim 4, wherein the step of peeling off the moisture-absorbing film is performed after the winding step.

6. The method according to any one of claims 1 to 5, wherein in the humidifying step, the hygroscopic film is humidified until the moisture content thereof reaches an equilibrium moisture content in an environment at a temperature of 20°C or higher and 80°C or lower and a relative humidity of 45% or higher.

Citation Information

Patent Citations

  • Polarizing plate, its manufacturing method, optical member, and liquid crystal display device

    JP2004245925A

  • Roll material and method for manufacturing roll material

    JP2009258661A

  • Cellulose acylate film and method for producing the same, retardation film, polarizing plate, and liquid crystal display device

    JP2010079239A

  • Method for manufacturing polarizing plate

    JP2016224392A

  • Method for manufacturing polarizing plate

    JP2016224423A